Enhancing High School Students’ Collaboration Skills and Learning Outcomes through PhET Simulation Based E-Worksheets in Sound Wave Topic - Mawarni Saputri; Nurulwati; Asmaul Husna (Tsaqila | Jurnal Pendidikan dan Teknologi, 2026)
This study was motivated by the low level of students' collaboration skills and physics learning outcomes and by the limited use of digital learning media that simultaneously promote both competencies. Therefore, this study aimed to examine the effect of PhET Simulation-based E-Worksheets on the collaboration skills and physics learning outcomes of eleventh-grade students at SMA Negeri 8 Banda Aceh. A quantitative approach employing a quasi-experimental pretest-posttest control group design was used. Two purposively selected classes participated as the experimental and control groups. Data were collected using pretest-posttest achievement tests, collaboration skills observation sheets, and student response questionnaires. The data were analyzed using descriptive statistics and an independent samples t-test. The results showed that students in the experimental class demonstrated higher collaboration skills than those in the control class. In addition, the experimental class achieved a higher mean physics learning outcome score (M = 76.66) than the control class (M = 65.00). The independent samples t-test indicated a significant difference between the two groups (t_count = 2.37 > t_table = 1.99), confirming that the use of PhET Simulation-based E-Worksheets significantly improved students' physics learning outcomes. These findings provide empirical evidence that integrating PhET Simulation with E-Worksheets not only enhances students' conceptual understanding of physics but also supports the development of collaboration skills, thereby offering an effective instructional strategy for twenty-first-century physics learning.